(untitled) (TRAKIA JOURNAL OF SCIENCES, 2025)
The research objective of this study is to establish the pedagogical benefits of a proven spinal-corrective methodology in game situations in the educational direction of "Physical Culture" in kindergarten conditions on preschool children, as well as to track their attitudes during the implementation of the innovative methodology of spinal-corrective complexes. This experimental study aims to track the pedagogical effect of the applied spinal-corrective methodology for correcting and preventing spinal curvatures. The subject of the study is the application of the complexes of corrective exercises for the correction and prevention of spinal curvatures according to a specially developed pedagogical methodology with pedagogical and innovative aspects. Research contingent: 100 children aged 5-6 years were studied, divided into two target groups: control and experimental. During the study, an experimental methodology of two spinal-correcting complexes was applied to the experimental target group.